A study on incidence of stress hyperglycemia in acute ischemic stroke in non-diabetic patients and its prognostic significance - Habibur Rahaman; Soumyasil Das; Angan Karmakar; Linkon Biswas; Subrata Kumar Pal (Asian Journal of Medical Sciences, 2022)
Background: Hyperglycemia detected during acute illness-like ischemic stroke is associated with adverse outcomes more than in normoglycemic patients. However,very limited data regarding stress hyperglycemia and its prognostic value are available for our Indian population. Aims and Objectives: This study was aimed at comparing the stress hyperglycemic and normoglycemic patients in terms of mortality and functional recovery during 28 days follow-up assessed by the Barthel index for Activities of Daily Living. Materials and Methods: Adult non-diabetic patients with ischemic stroke were assessed for random venous blood glucose and HbA1c levels and divided into two groups: Patients with hyperglycemia and normoglycemia. The Barthel Index for Activities of Daily Living was used to compare mortality and functional recovery on the day of admission, day 3, and day 28 after stroke. Results: Mortality over the 28 days follow-up was significantly higher in hyperglycemic patients (45% vs. 20%,P=0.02). The Barthel Index score on admission (day 0) was 8.75±7.41 among stress hyperglycemic patient whereas it was13.54±11.12 among normoglycemic patient, which was significantly different (P=0.028). Similarly, day 3 (18.89±6.08 vs. 23.26±13.05, P<0.05) and day 28 scores (83.24±7.49 vs. 84.55±12.84, P=0.039) were significantly better in normoglycemic patients. Conclusion: The mortality rate was much higher and functional recovery was much poorer in stress hyperglycemic patients. Further studies should be directed toward determining complications in long-term follow-up related to stress hyperglycemia and the effects of management on patient outcome.